2017
DOI: 10.1177/2192568216686753
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Outcomes of Vertebral Artery Injury in 16 582 Cervical Spine Surgery Patients: An AOSpine North America Multicenter Study

Abstract: Study Design:A multicenter retrospective case series was compiled involving 21 medical institutions. Inclusion criteria included patients who underwent cervical spine surgery between 2005 and 2011 and who sustained a vertebral artery injury (VAI).Objective:To report the frequency, risk factors, outcomes, and management goals of VAI in patients who have undergone cervical spine surgery.Methods:Patients were evaluated on the basis of condition-specific functional status using the Neck Disability Index (NDI), mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 32 publications
0
26
0
1
Order By: Relevance
“…The risk factors of VA injury include complex cervical deformity, narrow C2 pedicle, and VA path variation. 8 The preoperative imaging surveys include cervical spine X-ray, CT angiography, and cervical spine magnetic resonance imaging. Informed consent was given after oral explanation.…”
Section: Patient Inclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk factors of VA injury include complex cervical deformity, narrow C2 pedicle, and VA path variation. 8 The preoperative imaging surveys include cervical spine X-ray, CT angiography, and cervical spine magnetic resonance imaging. Informed consent was given after oral explanation.…”
Section: Patient Inclusionmentioning
confidence: 99%
“…In recent years, many studies have proved guiding template for pedicle screw insertion has high accuracy and safety in lumbar and thoracic spine. [8][9][10][11] In this study, we report our experience of performing atlantoaxial fixation in complex cervical deformity cases with 3D-customized guiding template.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown that with proper management, patients experience uneventful recovery without residual effects. [1] While neurologic deficits are rare complications of vertebral artery injury, when neurologic deficit occurs, they could be devastating and permanent. [1] Other severe outcomes are complications of stroke, pseudoaneurysm, late-onset hemorrhage, brain stem and cerebellar infarcts, and death; [1,5,8,9] early diagnosis and management are therefore critical to positive outcome.…”
Section: Introductionmentioning
confidence: 99%
“…An epidemiology study by Hsu et al [1] identified 14 cases, 0.08% of vertebral artery injuries in a multi-institutional database of 16,582 patients, a prevalence rate of 8.4 per 10,000. When examining penetrating trauma to the neck, the incidence has been reported as between 1.0-7.4%, with some variation attributed to mechanism (gunshot wound versus stab wound).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation